Designing smallholder-centric product and service bundles to incentivise technology adoption using an affordance perspective - Hoffman, Elena (2025)
Smallholder farmers in sub-Saharan Africa face complex and interrelated constraints that hinder the adoption of sustainable agricultural practices. Studies have shown that product and service bundles could serve as a solution to overcome multiple barriers smallholders face simultaneously, if designed appropriately. This study aims to design product and service bundles to incentivise the adoption of Mbili Mbili, a maize-legume intercropping practice, in Kasungu, Malawi. Using a smallholder-centric design approach grounded in design thinking and affordance theory, the research followed a three- step qualitative methodology process: identifying driver and barriers to adoption, mapping existing products and services, and co-developing and refining bundle prototypes with farmers. In doing so, this study extends the bundling literature by applying it to the adoption of agricultural practices rather than individual artefacts. Design thinking provided a structured, participatory framework for bundle development, while affordance theory served both as an analytical lens and a design tool, ensuring that bundle components aligned with farmers’ resources, constraints, and everyday realities.